Caesarean section in morbidly obese parturient: Technical difficulties - Das, Tanya; Saha, Rachana; Manandhar, Rosina (Journal of Kathmandu Medical College, 2020)
Approximately one third of women of reproductive age group are obese. Obesity significantly increases caesarean section rate. Not only is obesity associated with unfavourable clinical outcomes for both mother and childalso, performing caesarean sections in morbidly obese patients is a challenge for obstetricians, anaesthetists and the caregivers. In view of increased risks while performing Caesarean delivery in morbidly obese patient, this case report reviews the techniques and incisions used; the anaesthetic, logistical and practical challenges faced by the obstetricians while performing an emergency caesarean section in a women with BMI of 45.78kg/m2 who was also a diagnosed case of chronic hypertension with Grade I hypertensive retinopathy.